Pendidikan Berbasis Moderasi Beragama Berdasarkan Surat Al-Baqarah Ayat 143 - Ely Damayanti Pulungan; Widya Khairunnisa; M. Alfarabi; Ahmad Darlis (IAIN Bengkulu, 2023)
This article aims to find out the interpretation in Q.S Al-Baqarah: 143 which is related to religious moderation and to describe the educational values contained therein. The type of research used is a qualitative approach with the use of library research using books as themain source and journals as secondary sources as auxiliary sources that support this research.The findings of this study indicate that in Q.S Al-Baqarah: 143 M. Quraish Shibab and Buya Hamka explain that religious moderation is Muslim. It was further explained that religious moderation is an attitude that chooses a middle way, not being exaggerated nor too facilitating, not extreme nor liberal. In this case one can be balanced by keeping oneself busy with the world and not forgetting the hereafter. As for some educational values based on Q.S Al-Baqarah: 143 concerning religious moderation, namely instilling an attitude of justice within oneself, balance, mutual love, piety to Allah SWT and avoid violence.